2010
DOI: 10.4314/wajm.v28i6.55026
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Body Inhalation: A Review of Patients at the Korle Bu Teaching Hospital, Accra, Ghana

Abstract: BACKGROUND: Foreign body inhalation, a surgical emergency requiring prompt management to avoid morbidity and mortality , poses a diagnostic and management challenge to otolaryngologists. OBJECTIVE: To assess the pattern of foreign body inhalation at the ENT Unit Korle Bu Teaching Hospital Accra, Ghana. METHODS: The theatre records of patients managed for foreign body inhalation from Ist January 2003-31st December 2006 at the ENT Unit of the Korle Bu Teaching Hospital Accra, Ghana were studied with respect to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 7 publications
3
24
0
Order By: Relevance
“…The commonest organic FB inhaled in children is the groundnut and this concurs with our finding (25.7%) and is corroborated by other studies as well 1011162122. In contrast, a recent study in Kenya revealed that the commonest organic FB in their series was beans while the second were peanuts/groundnuts 6…”
Section: Discussionsupporting
confidence: 92%
“…The commonest organic FB inhaled in children is the groundnut and this concurs with our finding (25.7%) and is corroborated by other studies as well 1011162122. In contrast, a recent study in Kenya revealed that the commonest organic FB in their series was beans while the second were peanuts/groundnuts 6…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of right and left bronchial foreign bodies is almost equal in infants and young children (Mu et al 1990;Black et al 1994;Burton et al 1996;Cataneo et al 1997; Senkaya et al 1997;Metrangelo et al 1999;Oguz et al 2000;Van Looij et al 2003;Ayed et al 2003;Pinto et al 2006;Zhijun et al 2008;Cohen et al 2009;Rodriguez et al 2013), as opposed to predominance of the right bronchial tree in older children, adolescents, and adults (Baharloo et al 1999;Fraga Ade et al 2008;Roda et al 2008;Kitcher 2009;de Sousa et al 2009;Saki et al 2009;Falase et al 2013;Sidell et al 2013). These differences can partly be explained by the almost symmetrical tracheobronchial angle in younger children (Cleveland 1979) and by the position of the carina that is more commonly seen left to the midline (Tahir et al 2009).…”
Section: Mechanisms Of Airway Obstructionmentioning
confidence: 99%
“…Most cases of foreign body aspiration occur between the age of 6 months and 3 years, with the highest incidence during the second year of life (Mantel and Butenandt 1986;Piepsz 1988;Fitzpatrick and Guarisco 1998;Lima and Fischer 2002;Witt 1985;Roda et al 2008;Kitcher 2009;de Sousa et al 2009;Orji and Akpeh 2010;Pan et al 2012;Paksu et al 2012;Boufersaoui et al 2013;Sidell et al 2013;Tenjovic et al 2013). Infants and toddlers in this age group are already ambulatory and can therefore ''disappear'' from parent or guardian supervision for varying periods of time.…”
Section: Etiology/types Of Foreign Bodiesmentioning
confidence: 99%
See 2 more Smart Citations